Salvage preoperative embolization of an infratemporal solitary fibrous tumor: A case report with review of the literature. Issue 13 (March 2018) - Yammine, Kabalane; Nasser, Haydar A.; Hadi, Usama; Natout, Mohamad Ali; Najjar, Vicky; Tayar, Claude
Abstract: Rationale: Head and Neck Solitary fibrous tumors (SFT) are very rare. They could be misdiagnosed as hemangiopericytomas (HPC). Patient concerns: We report a 60 y o lady presenting with sinonasal mass, causing recurrent profuse bleeding. Diagnoses: Hemangioperocytomas versus SFT were among the differentials, according to Radiological studies. Upon Biopsy, the diagnosis of SFT has been adopted. Interventions: Salvage pre-operative embolization resulted in bleeding control, bridging the patient to surgery. Outcomes: Post-operative course was uneventful, and patient symptoms resolved. Lessons: This is the first case report of a sinonasal SFT, where pre-operative embolization has been employed as a salvage procedure. This treatment modality is promising, since it controls bleeding, bridges patient to surgery and decreases blood loss during the surgical procedure.